Study on the Pyrolysis Behaviour of Different Types of Tobacco and Their Pyrolytic Aroma Components Distribution Under Stepwise Heating Conditions - Jiang, Xi; Wu, Jian; Zhao, Lucan; Wang, Jun; Xiao, Weiqiang; Chen, Zhen; Jiang, Jian; Liang, Miao; Wang, Jiaqi; Zhang, Junsong (Flavour and fragrance journal, 2025)
Different types of tobacco should exhibit significant differences in pyrolysis behaviour and pyrolytic aroma components distribution due to their intrinsic microstructures and chemical composition features but rarely be compared. Herein, the pyrolysis characteristics of three types of tobacco (oriental tobacco, burley tobacco and flue‐cured tobacco) were studied by using thermogravimetric technique combined with thermal analysis kinetics method. The weight loss processes of each tobacco sample can be divided into four stages, namely dehydration, decomposition of volatile components, decomposition of hemicellulose and cellulose, and decomposition of lignin and carbonisation. Different types of tobacco exhibited various pyrolysis characteristic parameters in terms of T i , T f , DTG max , and CPI , indicating an obvious difference in the thermal decomposition characteristics of tobacco. And then a stepwise heating strategy was designed to in‐depth investigate the pyrolysis characteristics and release behaviour of aroma components at different thermal weight loss stages by using the self‐built infrared tube furnace combined with Cambridge filter capture system. The weight loss stages II and III would generate most of the aroma components for each type of tobacco. The release amount of oxygen heterocyclic and ketone compounds exhibited the order of flue‐cured tobacco (558.90 μg·g −1 ) > burley tobacco (423.44 μg·g −1 ) > oriental tobacco (291.55 μg·g −1 ) during the four stages. The release amount of nitrogen heterocyclic compounds exhibited the order of burley tobacco>flue‐cured tobacco>oriental tobacco, while the organic acids exhibited the opposite order. Furthermore, the physicochemical properties of biochar generated from different types of tobacco were characterised and compared by elemental analysis, Fourier transform infrared spectroscopy ( FTIR ) and scanning electron microscopy ( SEM ). This study may provide guidelines for the rational utilisation of different types of tobacco leaves in related products.